2012
DOI: 10.4187/respcare.01812
|View full text |Cite
|
Sign up to set email alerts
|

Volume-Time Curve: An Alternative for Endotracheal Tube Cuff Management

Abstract: BACKGROUND: Despite numerous studies on endotracheal tube cuff pressure (CP) management, the literature has yet to establish a technique capable of adequately filling the cuff with an appropriate volume of air while generating low CP in a less subjective way. The purpose of this prospective study was to evaluate and compare the CP levels and air volume required to fill the endotracheal tubes cuff using 2 different techniques (volume-time curve versus minimal occlusive volume) in the immediate postoperative per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
1
18
1
Order By: Relevance
“…The volume waveform may be useful to detect the presence of a leak (eg, bronchopleural fistula, leak around the cuff, leak around the mask), which results in a difference between the inspiratory and expiratory V T . Bolzan et al 34 reported a method for managing endotracheal tube cuff inflation using volume-time graphics.…”
Section: Tidal Volumementioning
confidence: 99%
“…The volume waveform may be useful to detect the presence of a leak (eg, bronchopleural fistula, leak around the cuff, leak around the mask), which results in a difference between the inspiratory and expiratory V T . Bolzan et al 34 reported a method for managing endotracheal tube cuff inflation using volume-time graphics.…”
Section: Tidal Volumementioning
confidence: 99%
“…We hypothesized that using the volume-time curve technique, which resulted in smaller cuff pressure after airway sealing, 3 could reduce the occurrence of endotracheal intubation-related respiratory symptoms, including sore throat, cough, and thoracic pain, secondary to a cough in patients submitted to coronary artery bypass grafting and a short period of mechanical ventilation, thus influencing the capacities and pulmonary volumes in the early postoperative phase.…”
Section: See the Related Editorial On Page 1810mentioning
confidence: 99%
“…During inflation, the examiner kept his ear 10 cm from the subject's mouth to ensure that there was no air leak. 3 Volume-Time Curve Group (n ‫؍‬ 228). The cuff was fully deflated and gradually inflated with a 20-mL syringe while the examiner analyzed the volume-time curve to generate a proper adjustment of air volume that should be…”
Section: Anesthesia and Operative Techniquementioning
confidence: 99%
See 2 more Smart Citations